Societal Transformations Aftermath COVID-19: An Overdue Exploration of Positive and Negative Impacts - Joshi, Yashoda Bhatta (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
COVID-19 pandemic has showcased profound changes across human society, altering various facets of social life. Beyond its immediate health implications, the pandemic has brought about powerful social transformations reshaping interpersonal dynamics, work patterns, and community adaptability. This research article examines multifaceted impact of COVID-19 on societies globally, considering its both positive and negative implications. Through a comprehensive review of literature and analysis of real-life scenarios, the study explores how the pandemic has reshaped social structures, behaviors, and attitudes. The paper concludes suggesting that the pandemic has deeply and diversely impacted the lives of people in general across the geographical boundaries by a complex interplay of consequences, highlighting the need to continuously navigate the post-pandemic social landscape.